Realizing Students with Islamic Good Character Outside of School: Teachers' Strategies in Rural Areas - Surahman, Buyung (Jurnal Ilmiah Syi'ar, 2022)
Students in rural areas turned out to have bad behavior while at school. There is a shift of responsibility from parents to religious teachers regarding student behavior. Parents tend to submit their children's religion to school. Meanwhile, teachers do not have enough time to form Islamic characters in students. This study describes the strategies used by Islamic religious education teachers while outside of school. This paper is essential to reveal a lesson for other teachers who experience similar problems. The State Elementary School in Sindang Dataran sub-district, Rejang Lebong Regency, has been appointed as the location for data collection. The methods used in data collection are documentation, interviews, and questionnaires. The results of this study are six out of nine Islamic religious education teachers make teacher strategies to realize students with good morals outside the classroom; the average application of the criteria for verbal speech is 65.5%, and the application of the requirements for physical activity is an average of 27.3%, while the application of using written messages/pictures/videos is only an average of 7.3%; the success of realizing student akhlakul karimah has not been maximized, because family and community heredity influence it. This study also discusses oral speech, physical treatment, and teacher messages in realizing akhlakul karimah students' outside the classroom.